Burkina Faso : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Extension of Commitment Period. (IMF Staff Country Reports; Country Report ;, 2006)
The staff report for the Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility on Burkina Faso highlights the macroeconomic framework for 2006 and the fiscal policy. Discussions on the macroeconomic framework for 2006 focused on the permanence of the record 2005/06 harvest. The authorities welcomed the debt relief provided under the Multilateral Debt Relief Initiative (MDRI), and indicated that they would use the additional resources to increase spending in priority social and infrastructure programs.